2003
DOI: 10.1149/1.1602083
|View full text |Cite
|
Sign up to set email alerts
|

An EQCM Study of the Electrochemical Copper(II)/Copper(I)/Copper System in the Presence of PEG and Chloride Ions

Abstract: The charge-transfer reaction between copper͑II͒ and copper electrodes is studied in electrolytes that are similar to galvanic copper baths, 2.2 M H 2 SO 4 ϩ 0.3 M CuSO 4 ϩ chloride ions (c Cl р 1 ϫ 10 Ϫ2 M͒, and polyethyleneglycol 1500 ͑PEG, c PEG р 4 ϫ 10 Ϫ3 M͒. Electrochemical quartz crystal microbalance ͑EQCM͒ measurements are conducted, mainly under conditions of cyclic voltammetry. The formation and dissolution of CuCl on the electrode surface at c Cl у 2 mM is demonstrated, a notable shift of the pseudo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 39 publications
4
79
0
Order By: Relevance
“…Higher Cl concentrations lead to precipitation of CuCl salt. 6 Voltammetric experiments in PEG solutions with Cl − concentrations significantly lower than 1 mM were reported by Jovic and Jovic, and are displayed in Fig. 1.…”
Section: Part Of the Chemical Engineering Commonsmentioning
confidence: 59%
“…Higher Cl concentrations lead to precipitation of CuCl salt. 6 Voltammetric experiments in PEG solutions with Cl − concentrations significantly lower than 1 mM were reported by Jovic and Jovic, and are displayed in Fig. 1.…”
Section: Part Of the Chemical Engineering Commonsmentioning
confidence: 59%
“…When both PEG and Cl − are present, a surface layer forms on the copper electrode that constitutes a barrier for charge transfer [2][3][4]. Healy et al suggested that the polymer can adsorb in two different ways.…”
Section: Introductionmentioning
confidence: 99%
“…The synergy of these additives stemmed from the adsorptive and transport characteristics of chloride ions and from the competitive interaction between the suppressor, accelerator, and leveler. 13,[35][36][37][38][39][40][41][42][43][44][45][46][47] In order to further analysis the function of Polyquaternium-2 in TH electroplating process, the addition sequence was changed again (the addition sequence followed the description in Table 1) and the result was shown in Fig. 9.…”
Section: Resultsmentioning
confidence: 99%